Nurses’ knowlwdge during monitoring of postpartum depression: Literature review (Research, Society and Development, 2023)
Objective: Analyze the available scientific literature with the aim of understanding what Postpartum Depression is and how nurses working in primary health care are prepared to identify it and monitor it. Methodology: A literature review was carried out, with scientific articles searched in the Virtual Health Library (VHL) with the following databases: IBECS, LILACS, MEDLINE and BDENF, using the descriptors “depression”, “postpartum”, “puerperium” and “nursing”. Results and Discussion: The final sample of this review consisted of 12 articles based on the previously selected inclusion criteria. Understanding the concepts, symptoms and risk factors associated with this condition is essential to promote greater awareness and support for women facing this experience. The mother may have difficulty interpreting her baby's physiological and emotional needs, such as hunger, sleep, discomfort and the need for affection and attention, which can result in inadequate or delayed responses. Final considerations: It is possible to conclude that in health units, team training must be a priority, in order to guarantee longitudinal care and the development of professional skills appropriate to monitoring the postpartum woman.